1975
DOI: 10.1172/jci108002
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine 3',5'-monophosphate and adenosine 3',5'-monophosphate content of human umbilical artery.

Abstract: A B S T R A C T Human umbilical arteries are unique vessels in that they close quickly and completely at birth. It

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
4

Year Published

1975
1975
1991
1991

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 23 publications
5
34
4
Order By: Relevance
“…Results with histamine blocking agents indicate that, as in the case of cAMP, metiamide, rather than pyrilamine, diminishes increases of cGMP in glomeruli. Such a finding differs from observations on smooth muscle preparations from umbilical arteries (33) (16).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Results with histamine blocking agents indicate that, as in the case of cAMP, metiamide, rather than pyrilamine, diminishes increases of cGMP in glomeruli. Such a finding differs from observations on smooth muscle preparations from umbilical arteries (33) (16).…”
Section: Discussioncontrasting
confidence: 99%
“…The incubation time employed in our experiments (2 min) was relatively short, in an attempt to detect changes not only in cAMP but also in cGMP, which are known from other systems to be transient, with a rapid onset, an early peak of the response, and with subsequent fast decline in time (32)(33)(34). In control experiments, (26), allowed measurements in small quantity of tissue; high specificity of anti-cAMP and anti-cGMP antibodies allowed simultaneous measurements ofboth cyclic nucleotides in the same tissue extract excluding cross-reactivity of cyclic nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…They therefore suggested that the umbilical arteries may have a poor relaxant response to cyclic GMP-mediated vascular relaxation. It has also been suggested that cyclic GMP accumulation in umbilical vessels induced by acetylcholine and histamine, may be associated with vascular contraction rather than relaxation (Clyman et al, 1975). Our results demonstrate that the umbilical and chorionic plate arteries do relax by cyclic GMP-mediated mechanisms although not as efficiently as other vessels under similar experimental conditions.…”
Section: Cyclic Gmp Accumulationmentioning
confidence: 99%
“…23 In our tests, no relaxation effect could be obtained with histamine on umbilical preparations mounted for isometric tension recording in the presence or absence of indomethacin and contracted with serotonin. However, Clymann et al 24 reported marked increases in cGMP levels in the human umbilical arteries in response to low concentrations of histamine, an effect that is also mediated by an H,-receptor mechanism, while they obtained only moderate increases in cGMP in response to serotonin and acetylcholine at high concentrations. This would indicate that EDRF also induces increased cGMP levels in the umbilical vessels but that there is only a poor response of these vessels to cGMP in contrast to other vascular smooth muscle cells.…”
mentioning
confidence: 98%